2019
DOI: 10.1371/journal.pone.0220193
|View full text |Cite
|
Sign up to set email alerts
|

The Strengths and Difficulties Questionnaire and standardized academic tests: Reliability across respondent type and age

Abstract: Exploiting nation-wide data from the Danish National Birth Cohort, we show that children’s emotional and behavioral problems measured by the Strengths and Difficulties Questionnaire (SDQ) are closely related to their performance in standardized academic tests for reading and mathematics in sixth grade. The relationship is remarkably linear across the entire distribution for both the total difficulties score and subscale scores of the SDQ; higher scores on the SDQ (more problems) are related to worse performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(20 reference statements)
5
4
0
1
Order By: Relevance
“…We find that the children with MHP independent of potential confounders perform statistically significantly worse at the 9 th grade exams, which are conducted about five years after the screening. This finding is in line with previous studies that have found an association between SDQ scores and school outcomes [21,22]. The results indicate that the screening algorithm succeed in identifying children that may benefit from an early intervention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We find that the children with MHP independent of potential confounders perform statistically significantly worse at the 9 th grade exams, which are conducted about five years after the screening. This finding is in line with previous studies that have found an association between SDQ scores and school outcomes [21,22]. The results indicate that the screening algorithm succeed in identifying children that may benefit from an early intervention.…”
Section: Discussionsupporting
confidence: 92%
“…The children’s later school performance is investigated as a primary indicator of the long-term outcome of the screening for MHP in preadolescence. As previous studies find an association between children’s MHP and their school performance [20–22], and school performance and schooling are known to be comprehensive predictors for the rest of a child’s life with respect to both wealth, health, and happiness [23–25], this indicator is well-suited for the evaluation of the screening. The children’s health care service utilisation during the five-year follow-up period is analysed for two purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Using the SDQ longitudinally across the same group of children has provided the opportunity to assess the validity, internal consistency, and reliability of the SDQ at various points in time but with the added advantage of using the same population of children. In general, we found the factor structure to be consistent over time, supporting earlier studies [11]. Similarly, the reliability of the Total Difficulties Score and each of the sub-scales is good and again in line with previously published cross sectional data [8,9,26].…”
Section: Discussionsupporting
confidence: 91%
“…Similar reliability has also been shown in other populations [8,9] and ages [10,11]. A review with 48 studies confirmed that the SDQ is a psychometrically sound measure of child mental health and behavioural problems [12] and can be used to predict standardised academic performance [11] and psychopathology [13]. Data from a large sample of 3-5 year old German preschool children also confirmed the 5-factor solution as the best fit of the data, and confirmed the usefulness of the screening tool for young children [14].…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation